College students’ consumption behavior: the role of financial literacy and e-wallet usage - Meyfi Christin Rezky Baman; Chalarce Totanan; Ni Made Suwitri Parwati; Mohammad Iqbal Bakry (Institute of Accounting Research and Novation (IARN), 2026)
This study purpose to asses the impact of financial literacy and e-wallet usage on college students’ consumptive behavior of active undergraduate students in the accounting department at the Faculty of Economics and Business, Tadulako University, from the classes of 2022, 2023, 2024, and 2025. Sample for this study consisted of 210 people selected by purposive sampling, with data collected by questionnaire delivered using g-forms. Data was analyzed using multiple linear regression with SPSS 27 software. Analysis results that the financial literacy does not have a significant effect on students’ consumptive behavior, however e-wallet usage has a significant effect on students’ consumptive behavior. This study illustrates that convenience of using digital wallets can influence students’ purchasing habits. As a result, more financial literacy is requires to guarantee that digital financial technology is used wisely.